The identification of skills and competencies for effective management in social enterprises. A managerial perspective - Wronka-Pośpiech Martyna (Management, 2016)
The need to adapt to external business requirements, turbulences present in the environment as well as the dynamic changes occurring in the non-profit sector require the presence of managers who are not only capable of taking proper care of financial issues, but also of optimally deploying available human resources. Today, organisations operate in the world without fixed rules of conduct or a universal management style. As a consequence, there is no universal recipe for success. It is, however, clear that the social enterprise should be run by a competent manager, preferably someone with a business track record and in-depth knowledge of formal issues. The literature review shows that working in a social enterprise requires a high degree of flexibility, a variety of skills and qualifications with the management facing a difficult challenge of how to simultaneously achieve social and economic objectives. The purpose of this article is to identify and explore the key competences and optimal features of the social enterprise manager. Data for the study was collected through a survey from 100 social enterprises in Poland.